Effectiveness and safety of SARS‐CoV‐2 vaccine in Inflammatory Bowel Disease patients: a systematic review, meta‐analysis and meta‐regression. Issue 10 (30th March 2022) - Bhurwal, Abhishek; Mutneja, Hemant; Bansal, Vikas; Goel, Akshay; Arora, Shilpa; Attar, Bashar; Minacapelli, Carlos D.; Kochhar, Gursimran; Chen, Lea Ann; Brant, Steve; Seril, Darren
Abstract: Introduction: There are concerns regarding the effectiveness and safety of SARS‐CoV‐2 vaccine in inflammatory Bowel Disease (IBD) patients. This systematic review and meta‐analysis comprehensively summarises the available literature regarding the safety and effectiveness of SARS‐CoV‐2 vaccine in IBD. Methods: Three independent reviewers performed a comprehensive review of all original articles describing the response of SARS‐CoV‐2 vaccines in patients with IBD. Primary outcomes were (1) pooled seroconversion rate SARS‐CoV‐2 vaccination in IBD patients (2) comparison of breakthrough COVID‐19 infection rate SARS‐CoV‐2 vaccination in IBD patients with control cohort and (3) pooled adverse event rate of SARS‐CoV‐2 vaccine. All outcomes were evaluated for one and two doses of SARS‐CoV‐2 vaccine. Meta‐regression was performed. Probability of publication bias was assessed using funnel plots and with Egger's test. Results: Twenty‐one studies yielded a pooled seroconversion rate of 73.7% and 96.8% in IBD patients after one and two doses of SARS‐CoV‐2 vaccine respectively. Sub‐group analysis revealed non‐statistically significant differences between different immunosuppressive regimens for seroconversion. Meta‐regression revealed that the vaccine type and study location independently influenced seroconversion rates. There was no statistically significant difference in breakthrough infection in IBD patients as compared to control after vaccination. Conclusion: In summary, the systematic review and meta‐analysis suggest that SARS‐CoV‐2 vaccine is safe and effective in IBD patients.